The artificial pancreas: evaluating risk of hypoglycaemia following errors that can be expected with prolonged at‐home use. Issue 2 (4th July 2015) - Wolpert, H.; Kavanagh, M.; Atakov‐Castillo, A.; Steil, G. M.
Abstract: Aims: Artificial pancreas systems show benefit in closely monitored at‐home studies, but may not have sufficient power to assess safety during infrequent, but expected, system or user errors. The aim of this study was to assess the safety of an artificial pancreas system emulating the β–cell when the glucose value used for control is improperly calibrated and participants forget to administer pre‐meal insulin boluses. Methods: Artificial pancreas control was performed in a clinic research centre on three separate occasions each lasting from 10 p.m. to 2 p.m. Sensor glucose values normally used for artificial pancreas control were replaced with scaled blood glucose values calculated to be 20% lower than, equal to or 33% higher than the true blood glucose. Safe control was defined as blood glucose between 3.9 and 8.3 mmol/l. Results: Artificial pancreas control resulted in fasting scaled blood glucose values not different from target (6.67 mmol/l) at any scaling factor. Meal control with scaled blood glucose 33% higher than blood glucose resulted in supplemental carbohydrate to prevent hypoglycaemia in four of six participants during breakfast, and one participant during the night. In all instances, scaled blood glucose reported blood glucose as safe. Conclusions: Outpatient trials evaluating artificial pancreas performance based on sensor glucose may not detect hypoglycaemia when sensor glucose reads higher than blood glucose. Because these errors are expected to occur, in‐hospital artificial pancreas studies using supplemental carbohydrate in anticipation of hypoglycaemia, which allow safety to be assessed in a controlled non‐significant environment should be considered as an alternative. Inpatient studies provide a definitive alternative to model‐based computer simulations and can be conducted in parallel with closely monitored outpatient artificial pancreas studies used to assess benefit. What's new?: A novel method to assess the impact of sensor and other errors on the safety of an artificial pancreas is introduced in which sensor glucose values normally used for control are replaced with near‐perfect minute‐to‐minute glucose values calculated from reference blood glucose values, and errors that reflect infrequent, but expected, events are added to the signal. We show that an artificial pancreas system emulating the β–cell is safe when the correct glucose values, or values 20% lower than correct are used, but that values 33% higher than correct result in control that is too aggressive to be considered safe.